Yoghurt kedelai hitam (black soyghurt) dapat menurunkan kadar LDL tikus hiperkolesterolemia - Slamet Riyanto; Hesti Muwarni R (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2015)
ABSTRACTBackground: Hypercholesterolemia is a main risk factor of cardiovascular disease that remains the higher cause of deaths in the world. Black soy bean containing protein, fiber, vitamin, isoflavon, and flavonoid can decrease serum cholesterol level. Yoghurt contains lactic acid bacteria that decrease total and LDL cholesterol, triglyceride, and increase the HDL cholesterol. Processing of black soy bean into black soyghurt can increase its isoflavon’s activity by forming aglicone, which has higher activity to decrease cholesterol.Objectives: To know the effect of black soyghurt feeding to LDL, HDL, and HDL ratio of hypercholesterolemic rats.Methods: This research was true-experimental using post test only with control group design. Subjects were 20 male Sprague dawley rats, 2 months old, inducted hypercholesterolemia, given black soyghurt diet using 2 mL, 3 mL, and 4 mL dosage for 21 days. Serum lipid profile were measured by CHOD-PAPand GPO-PAP methods respectively. Normality of the data were tested by Shapiro Wilks test. Data were analyzed by paired t test and Anova continued by LSD test using computer program.Results: The study revealed that black soyghurt 4 mL/day decreased LDL (p=0.02) at the most significant level. The other doses did not significantly influence the levels of LDL (p>0.05 ). There was also no effect of black soyghurt feeding on serum HDL cholesterol levels (p=0.11) and the ratio of LDL /HDL (p=0.087).Conclusions: The feeding of black soyghurt at the dosage of 4 mL/day to hypercholesterolemic rats could decrease the serum LDL, but could decrease the ratio of LDL / HDL significantly.KEYWORDS: black soyghurt, LDL/HDL ratio, hypercholesterolemicABSTRAKLatar belakang: Hiperkolesterolemia merupakan faktor risiko penyakit kardiovaskuler yang menjadi penyebab kematian utama di dunia. Kedelai hitam mengandung protein, vitamin, serat, isoflavon, dan flavonoid yang mampu menurunkan kadar kolesterol. Yoghurt mengandung bakteri asam laktat yang mampu menurunkan kadar kolesterol total, LDL, dan trigliserida serta meningkatkan HDL. Pengolahan kedelai hitam menjadi black soyghurt meningkatkan aktivitas isoflavon dalam kedelai hitam menjadi aglikon yang lebih tinggi aktivitasnya dalam menurunkan kolesterol.Tujuan: Untuk mengetahui pengaruh pemberian yoghurt kedelai hitam terhadap kadar LDL, HDL, dan rasio LDL/HDL pada tikus hiperkolesterolemia.Metode: Jenis penelitian ini adalah true-experimental dengan post test only with control group design. Subjek penelitian adalah 20 tikus Sprague dawley jantan berusia 2 bulan, diinduksi hiperkolesterolemia, diberi black soyghurt dosis 2 mL, 3 mL, dan 4 mL selama 21 hari. Profil lipid diperiksa dengan metode cholesterol oxidase-peroxidase aminoantipyrine phenol (CHOD-PAP). Normalitas data diuji dengan Shapiro Wilks. Data dianalisis dengan uji t berpasangan dan Anova, dilanjutkan uji least significant difference (LSD) menggunakan program komputer. Hasil: Pemberian black soyghurt dosis 4 mL/hari mampu menurunkan kadar LDL (p=0,002) paling signfikan. Dosis pemberian lain tidak berpengaruh secara signifikan terhadap kadar LDL (p>0,05). Pemberian pakan tersebut juga tidak berpengaruh terhadap kadar kolesterol HDL serum hewan coba (p=0,11), dan rasio LDL/HDL (p=0,087).Kesimpulan: Diet mengandung black soyghurt dosis 4 mL/hari dapat menurunkan LDL, tetapi tidak mampu menurunkan rasio LDL/HDL secara signifikan.KATA KUNCI: black soyghurt, rasio LDL/HDL, hiperkolesterolemia